Identification of a novel KCNT2 variant in a family with developmental and epileptic encephalopathies: a case report and literature review - Cui, Fengji; Wulan, Tuoya; Zhang, Qian; Zhang, Victor Wei; Jiang, Yuhua (Frontiers in Genetics, 2024)
Background: Developmental and epileptic encephalopathies (DEEs) are a group of heterogeneous neurodevelopmental diseases characterized mainly by developmental delay/intellectual disability and early-onset epilepsy. Researchers have identified variations in the KCNT2 gene (OMIM* 610044) as the cause of DEE type 57 (MIM# 617771).We report in this study a 46-year-old woman who presented with early-onset epilepsy, intellectual disability, hypertrichosis, coarse facial features, and short stature. Besides, there were four other affected individuals in her family history, including two elder brothers, a younger brother, and their mother. We collected blood samples from the proband, her two affected brothers, and her clinically normal daughter for genetic analysis. Clinical exome sequencing revealed a novel heterozygous variant in the KCNT2 gene (NM_198503: c.188G>A, p.Arg63His) in the proband and her two affected brothers, while her daughter did not carry this variant. Furthermore, we reviewed all 25 patients identified in the literature with KCNT2 variants and compared their phenotypes.Epilepsy and intellectual disability/developmental delay occur in almost all patients with KCNT2 variants. KCNT2-relevant DEEs partially overlap with the clinical phenotypes of KATP channel diseases, particularly in hypertrichosis and distinctive coarse facial features.